"Why my students didn't read according to their level?": An instructor's reflection in an extensive reading class - Nugrahenny T. Zacharias (Indonesian JELT, 2016)
The present paper is a novice teacher reflection in an Extensive Reading (ER) course. It attempts to explore the extent to which reflecting on critical incident of a reading level contributes to new understanding of Day and Bamford’s ER principles utilized to design the course. This study found that reflection through critical incidents provides a systematic structure to develop practical pedaogigcal knowledge into teaching. By exercising a critical incident reflection on ER, I was able to critically contextualize Day and Bamford’s ER principles into my current teaching context. It concludes by pointing out how a narrative reflection on critical incidents is needed to understand a novice teacher’s experience when practicing a new approach in teaching.